Atom-by-atom searching using massive parallelism. Implementation of the Ullmann subgraph isomorphism algorithm on the distributed array processor - Willett, Peter; Wilson, Terence; Reddaway, Stewart F (Journal of chemical information and computer sciences, 1991)
Describes the implementation of atom-by-atom searching of chemical structures and substructures using the Ullmann Subgraph Isomorphism Algorithm on the Distributed Array Processor. 00 Original abstract--amended